Kinematic characteristics of resisted sled sprints under different loading conditions - Osterwald, K. M.; Kelly, D.; Braga Rodrigues, T.; O'Cathain, C. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to identify the kinematic characteristics of resisted sled sprinting under different loading conditions (0%, 10%, 20% and 30% velocity decrement (Vdec)) and in different sporting populations. Thirty-three healthy athletes (Sprinters n=10; Invasion team sport athletes n=23) were recruited and completed 3 days of testing. Kinematics were captured with high-speed cameras and processed using Dartfish Software. Loads of 20% and 30% Vdec resulted in a significant increase in trunk lean relative to unloaded sprinting, during both acceleration and maximum velocity phases, with no difference between groups (sprint & team sport athletes). This increase in trunk lean with load (20% and 30% Vdec) appeared to prevent athletes transitioning into upright maximum velocity mechanics, and therefore extended the distance of the acceleration phase. The trunk lean increase was related to the heavy loads and athletes were not able to reach mechanics that were truly reflective of maximum velocity (maxV) sprinting. However, heavy loading extended the distance over which it is possible to train acceleration